Dosage Effects in the Child-Parent Center PreK-to-3rd Grade Program: A Re-analysis in the Chicago Longitudinal Study. (June 2019) - Ou, Suh-Ruu; Arteaga, Irma; Reynolds, Arthur J.
Abstract: Although substantial investments in early childhood intervention have continued, whether gains are sustained past kindergarten for routinely implemented programs is a critical research need. Using data from the Chicago Longitudinal Study (CLS; N = 1539; 50.3% female; 92.9% African American and 7.1% Hispanic), an on-going investigation of the Child-Parent Center (CPC) program for an inner-city cohort, this study investigates the effects of program duration from preschool to 3rd grade on school outcomes and whether the effects differ by gender. Regression analyses are conducted to compare the differences in outcomes among intervention groups. Inverse probability weighting (IPW) is used to adjust for potential attrition and selection biases. Findings indicate that relative to the preschool plus kindergarten (P-K) group, participation from preschool through third grade (P-3) is significantly associated with better academic functioning at both 3rd and 8th grades, better classroom adjustment at 3rd grade, lower rates of retention and school mobility, and few years of special education. Relative to the preschool through second grade (P-2) group, the P-3 group has significantly higher academic functioning in third grade. Results suggest that the P-3 dosage is associated with larger effects on academic functioning for girls and larger effects on social-emotional functioning for boys compare to the P-K dosage. Findings suggest that receiving up to third grade (P-3) of an early childhood education program have associated with persistent effects on developmental outcomes compared to the dosages of P-K. Multi-year programs have the potential to sustain early childhood gains and promote healthy development via improving academic functioning and school experiences. Highlights: P-3 dosage is associated with better school outcomes than P-K, P-1, or P-2 dosage. Performance of the P-K group is not different from no intervention, K-3 or P-1 groups. Boys are driving the P-3 effects in social-emotional functioning. K-3 dosage is associated with 2 outcomes positively than P-K dosage for girls. Girls not participating in CPC are associated with higher rates of school mobility.